PEMBUATAN TAPE UBI JALAR UNGU (Ipomoea batatas var Ayamurasaki) BERDASARKAN LAMA FERMENTASI SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PADA PEMBELAJARAN BIOLOGI SMA - Fahrizal, Yustri; ', Darmawati; ', Wansyafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim to find out the results fermentation tape purple sweet potato (Ipomoea batatas var. Ayamurasaki) by fermentation in March to June 2016. The results are used to design the work sheet concept of biotechnology conventional in senior high school class XII. This research do in two phases: making tape using experimental research and design worksheet. Research experiments were conducted using a completely randomized design, which consists of 6 treatments and 3 replicates in order to obtain 18 experimental design. If there is a difference between treatments then tested the Duncan Multiple Range Test (DMRT) at 5% level. The observed parameters alcohol content, moisture content, pH, organoleptic (taste, aroma, color and texture). The results showed that the longer the fermentation time a significant effect on alcohol content, moisture content, pH, organoleptic taste, aroma, color and texture tape purple sweet potato (Ipomoea batatas var. Ayamurasaki). Best long fermentation time is 36 hours which had a mean alcohol content of 1.23%, the water content of 74.47%, the average pH value of 3.41 and a yield of organoleptic favored by consumers. Results of the research have the potential to design worksheet on the concept of conventional biotechnology on the subjects of high school biology class XII.Keywords: Tape purple sweet potato, long fermentation, worksheet